The Duke of Abruzzi's Noble Idea of Winning the North Pole for Italy: Popularization of the Arctic Expedition Led by Luigi Amedeo of Savoia. (4th May 2019) - Cauli, Alberto
Abstract : At the beginning of the twentieth century, Luigi Amedeo of Savoia, the Duke of Abruzzi, planned and led the first Italian Arctic expedition with the purpose of reaching the Pole. His endeavor marked an important step in this race, which until the mid-nineteenth century had mainly involved explorers from Britain, the United States, and the Nordic nations. The Italian attempt gained international attention both for the Duke and Italy, despite its failure. To understand the expedition's significance in the media and popular culture, this article analyzes Luigi of Savoia's figure in the narrative of polar feats that took place in the nineteenth century. It reconstructs the reasons for the Duke's Arctic voyage and examines how the Italian and the international press represented the endeavor, contributing to its popularization. It also analyzes the cultural legacy of the Duke and his enterprise in modern Italy.